Enhancing Safety Awareness through Oil and Gas Occupational Health Training for Students in Blora and Bojonegoro - Susilo Handoko; Budi Sulistiyo Nugroho; Totok Widiyanto; Kasturi Kasturi; Ferro Aji; Sujono Sujono; Hernawan Noviyanto; Haris Numan Auli; Astrie Kusuma Dewi; Erdila Indriani (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
Blora and Bojonegoro, as regions with intensive oil and gas activities, require strengthened community safety capacity, especially among students. This study evaluates the effectiveness of a community-based occupational health and safety training program using an experiential learning approach. The three-day program included interactive lectures, group discussions, and simulations involving fire extinguishers, fire blankets, sound level meters, and multi-gas detectors. Evaluation employed validated pre-tests and post-tests, along with a structured skills assessment rubric. Results indicate a 53.9% increase in safety knowledge, with 93% of participants demonstrating proper use of fire extinguishers and fire blankets. Qualitative findings show improved risk awareness and confidence. These results align with experiential learning theory and social learning theory, and are consistent with recent studies confirming the effectiveness of safety simulations. The study concludes that community-based occupational health and safety training effectively improves student safety competence in oil and gas regions and can be replicated in other high-risk sectors. Recommendations include periodic simulation-based training, creation of school and village safety volunteer teams, integration of occupational health and safety life skills into school curricula, and longitudinal evaluation of knowledge and behavior retention.